Impact of regular consumption of millets on fasting and post-prandial blood glucose level: a systematic review and meta-analysis - Anitha, Seetha; Tsusaka, Takuji W.; Botha, Rosemary; Givens, D. Ian; Rajendran, Ananthan; Parasannanavar, Devraj J.; Subramaniam, Kowsalya; Bhandari, Raj Kumar; Kane-Potaka, Joanna (Frontiers Media, 2024)
Millets have a low Glycemic Index and are thus expected to help reduce concentration of Fasting and Post-Prandial Blood Sugar (FBS and PPBS) and glycated hemoglobin (HbA1c), which can potentially help the management of type 2 diabetes. This study conducts a systematic review and meta-analysis of the effects of millets consumption on FBS, PPBS, and HbA1c levels in comparison to major staple diets using the difference-in-differences (DID) method, where the effect size was computed on the Standardized Mean Difference scale. Among twelve eligible articles, ten were used in the meta-analysis to assess the effects on FBS levels, while five were used to assess the effects on PPBS levels. The results show significant effects on FBS (p andlt; 0.01) and PPBS (p andlt; 0.05) levels with the effect size of −0.71 and −0.42, respectively. There were 11.8% (p = 0.001) and 15.1% (p = 0.012) reductions in FBS and PPBS level respectively observed in the millet consuming group whereas the comparator group did not have significant reductions in either indicator. On the other hand, the effects on HbA1c levels were insignificant, presumably due to the small sample size where only two studies were undertaken over 90 days, which warrants further research. The findings corroborate the evidence that millets can contribute to managing FBS and PPBS levels better than major staple diets, implying that millets consumption helps reduce the risk of type 2 diabetes.